Tantangan dan Peluang Implementasi Kurikulum 2013 pada Mata Pelajaran Pendidikan Agama Islam di Era Digital Di MAN 7 Depok - Kosasih, Muhamad; Zikrulloh, Muhamad; Kartika, Ika (At-Tadris: Journal of Islamic Education, 2025)
Implementation of the 2013 Curriculum in Islamic Religious Education (PAI) subjects at MAN 7 Depok in the digital era presents unique challenges and opportunities. This research aims to identify challenges and opportunities in implementing the 2013 Curriculum in Islamic Religious Education (PAI) subjects at Madrasah Aliyah Negeri 7 Depok. The research method used is qualitative with a descriptive approach. Data collection was carried out through observation, interviews and documentation. The research method used in this research uses qualitative research. Data was collected through observation, in-depth interviews and documentary studies. Data analysis was carried out through data reduction, interpretation, conclusions and verification. The research results show that there are several challenges faced, including a lack of teacher training in the use of technology, limited facilities and infrastructure, and a lack of digital-based PAI teaching materials. However, on the other hand, there are also opportunities that can be exploited, such as the use of various digital platforms for learning, the development of interactive teaching materials, and collaboration with various parties to improve the quality of PAI learning. To face challenges in improving the curriculum, it is necessary to develop character, critical thinking and 21st century skills, which have the potential to form students who are religious and competitive. However, its implementation in the digital era is also faced with several challenges, such as limited access to technology, the digital gap between teachers and students, and a lack of digital literacy in the use of learning technology.